Influence on performance and emission characteristics of diesel engine by introducing medium strength magnetic field in fuel and air lines. Issue 1 (February 2020) - Chandrasekaran, M; Prakash, KB; Prakash, S; Ravikumar, M
Abstract: Manufacturing In this work, the energy of electromagnet is used to treat the fuel and airline for reducing the fuel consumption and emissions in four-stroke diesel engine. The experiment comprises Internal Combustion (IC) Engine test rig and electromagnets with different intensities (4500, 6000, 8500 and 10000 gauss), are installed along the honeycomb structured mini channel fuel line and air suction line. Experiments are carried out in four-stroke diesel engine test rig for variable engine load by applying medium strength magnetic field on air and fuel supply line. The medium strength magnetic field is used to improve the atomization process effectively, due to that increment in the rate of disintegration of the droplets, as result the viscosity of the fuel decreases. Because of cohesive force between the fuel molecules are affected by the magnetic field and it leads to less surface tension force effect, thus helps to improve atomization process. It is observed that, the impact of magnetic field treatment considerably increased the brake thermal efficiency about 13% and maximum fuel reduction of 11% was obtained for field intensity 10000G and also found that the HC, CO, PM, and NOx emissions are decreased about 10.4%-14.2%, 24–25%, 13%–15%, and 8.4%-11% respectively, but CO2 is increased up to 12.2% because of association of oxygen molecules with CO which is critical point and it can be treated in the catalytic converter.